Pemberdayaan Umkm Desa Melalui Pelatihan Legalitas Usaha Dan Desain Branding Di Desa Merangin Kabupaten Kampar - Ilham Radhifa; Rinda Elni Septari; Verdhitia Ikhsan Pratama; Aulia Rahma; Afifah Cahyani; Risni Ramadhani; Revaliza Syahinda; Mhd Farhan; Ikbal Ardiansyah Purba; Encik Rania Olivia; Nadhila Irawan; Riska Febrianda; Egi Chandra; Nurmaizar Nurmaizar; Bastian Felix Hutagaol; Nadia Asti Nurmayzana; Frini Karina Andini (Unri Conference Series: Community Engagement, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in villages have great potential to support the local economy, but they still face various challenges, such as the lack of business legality and weak product branding. In Merangin Village, Kampar Regency, most MSME actors run their businesses informally without a Business Identification Number (NIB), have unsystematic financial records, and use unattractive product packaging. This activity aims to strengthen the capacity of MSMEs through intensive training and mentoring that covers business legality, basic management, and branding design. The methods used include theoretical material delivery, practical simulations, and collaboration between lecturers and Kukerta students in providing personal assistance to participants. The results show that participants were able to understand and register for NIBs through the OSS platform, prepare a Business Model Canvas (BMC), calculate the cost of production (HPP), and conduct simple financial recording. In addition, participants also succeeded in designing product logos and packaging that are more appealing by utilizing online design applications. This activity proves that a collaborative and practical approach is highly effective in improving the knowledge and skills of village MSMEs, enabling them to be better prepared to compete in broader markets and operate with formal legality.